Supportive and Palliative Care: Addressing the Unspoken Burden of Cancer on Significant Others - Esmeraldo De Las Armas, IV (Jurnal Keperawatan Indonesia, 2026)
A diagnosis such as cancer can cast a long-lasting gloom that affects not only the patient but also their loved ones. This concept analysis represents an effort to understand and explore the nuanced world of supportive and palliative care for significant others of cancer patients, a population that has often been overlooked. Rodgers’ evolutionary model of concept analysis was utilized to examine the concept of supportive and palliative care for significant others of cancer patients. Positive outcomes for both significant others and patients included improved coping mechanisms, reduced caregiver burden, enhanced communication, and better quality of life. However, several challenges remain, including limited access to and awareness of these services. In addition, societal stigma surrounding palliative care and the traditional patient-centered focus may hinder broader integration of such services.